Penerapan Green Manufacturing dalam Pemberdayaan Masyarakat oleh Mahasiswa Guna Mendukung Pangan Berkelanjutan Desa Kebakalan - Susastriawan, Anak Agung Putu; Defta, Alaselo; Naufal, Moh. Akbar; Rahayu, Suparni S.; Rachmawati, Yuliana (Journal of Dedicators Community, 2025)
In terms of maintaining and increasing soil productivity, a combination of inorganic fertilizers with the right organic fertilizers is needed. The use of organic fertilizers can improve the quality of the soil in terms of physical, chemical and biological properties of the soil as well as nutrients for plants. Nutrients that are quite high and complete make organic fertilizers can be used as a source of nutrients for plants. The importance of organic fertilizers in restoring soil fertility underlies the implementation of community empowerment programs by students in mentoring and transferring composting technology using drum composter media for farmer groups in Kebakalan Village, Karanggayam, Kebumen, Central Java. This composting assistance was attended by 4 farmer groups from Kebakalan Village. The implementation method is starting from training on how to make drum composters and training on how to make compost. The results of this training can be seen from the interest and ability of participants in following, making, and applying compost to plants.